2022
DOI: 10.3389/fmolb.2022.919187
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Roles of Ferroptosis in Lung Diseases

Abstract: Ferroptosis is a distinct type of programmed cell death (PCD) that depends on iron and is characterized by the accumulation of intracellular iron, exhaustion of glutathione, deactivation of glutathione peroxidase, and promotion of lipid peroxidation. Recently, accumulated investigations have demonstrated that ferroptosis is strongly correlated with the initiation and development of many lung diseases. In this review, we summarized the contribution of ferroptosis to the pathologic process of lung diseases, name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 152 publications
0
20
0
Order By: Relevance
“…Ferroptosis, a new type of necrotic cell death, is characterized by an iron‐dependent accumulation of lipid peroxides (LPOs) and redox imbalance (Lei et al, 2019, 2020; Yan et al, 2021). Recent studies have demonstrated that ferroptosis of respiratory epithelial cells is implicated in the pathogenesis of COPD (Li et al, 2022; Yang et al, 2022; Yoshida et al, 2019). Several etiological agents of COPD such as cigarette smoke (CS) can induce the accumulation of labile iron via induction of ferritinophagy, thereby resulting in an iron‐dependent production of LPOs via Fenton reaction (Yoshida et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis, a new type of necrotic cell death, is characterized by an iron‐dependent accumulation of lipid peroxides (LPOs) and redox imbalance (Lei et al, 2019, 2020; Yan et al, 2021). Recent studies have demonstrated that ferroptosis of respiratory epithelial cells is implicated in the pathogenesis of COPD (Li et al, 2022; Yang et al, 2022; Yoshida et al, 2019). Several etiological agents of COPD such as cigarette smoke (CS) can induce the accumulation of labile iron via induction of ferritinophagy, thereby resulting in an iron‐dependent production of LPOs via Fenton reaction (Yoshida et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the activation of pSTAT3 inhibits OGD/R-induced ferroptotic damage in MLE12 cells and pathological processes associated with ALI by modulating SLC7A11 [ 156 ]. Irisin, a muscle-derived myokine with potent protective effects, inhibits ferroptosis in pulmonary IRI both in vitro and in vivo [ 157 ]. Consistent with the action of Fer-1, inhibition of ferroptosis in pulmonary IRI by irisin was manifested by lower ROS, MDA, and Fe 2+ levels and increased the expression levels of GPX4, which was achieved by promoting NRF2/HO-1 signaling.…”
Section: Mechanisms and Targeted Therapies For Ferroptosis In Irimentioning
confidence: 99%
“…[10][11][12] The involvement of ferroptosis has been found in many pathological conditions of the lung, such as acute lung injury, pulmonary fibrosis, asthma, chronic obstructive pulmonary disease, pulmonary hypertension and tuberculosis. 13 Several ferroptosis regulators, including iron homeostasis regulators and lipid peroxidation inhibitors, have been shown to have therapeutic effects on acute lung injury. 14 A large amount of iron is reported to be deposited in the lung tissue of patients with pulmonary fibrosis, which induces iron death and promotes the development of pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis, comprising a form of programmed cell death that was first reported in 2012, is characterized by the overwhelming, iron‐dependent accumulation of lethal lipid reactive oxygen species 10–12 . The involvement of ferroptosis has been found in many pathological conditions of the lung, such as acute lung injury, pulmonary fibrosis, asthma, chronic obstructive pulmonary disease, pulmonary hypertension and tuberculosis 13 . Several ferroptosis regulators, including iron homeostasis regulators and lipid peroxidation inhibitors, have been shown to have therapeutic effects on acute lung injury 14 .…”
Section: Introductionmentioning
confidence: 99%